Electrolytic copper foil and its manufacturing method, negative electrode plate, secondary battery, battery module, battery pack, and power consumption device
Patent Information
- Application Number
- JP2023531543
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-09-10
- Filing Date
- 2022-05-18
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-05-18
Smart Images

Figure 0007622220000004 
Figure 0007622220000005 
Figure 0007622220000006
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to Chinese patent application number 202111062005.3, entitled "Electrolytic copper foil and its manufacturing method, negative electrode plate, and secondary battery," filed on September 10, 2021, the entire contents of which are incorporated herein by reference. [Technical field]
[0002] The present application belongs to the technical field of secondary batteries, and specifically relates to an electrolytic copper foil and its manufacturing method, a negative electrode plate, a secondary battery, a battery module, a battery pack, and a power consuming device. [Background technology]
[0003] Copper foil is often used as the negative electrode current collector of secondary batteries, and the currently used copper foil mainly includes rolled copper foil by rolling process and electrolytic copper foil by plating process. Rolled copper foil has high requirements for production technology, complicated process, high cost, and is not suitable for large-scale production, so people are gradually shifting the focus of research to electrolytic copper foil. However, in order to meet the high mass energy density requirements of current secondary batteries, it is necessary to make the thickness of electrolytic copper foil thinner and ensure sufficient tensile strength and hardness. The mechanical performance of traditional electrolytic copper foil is already unable to meet the requirements of high mass energy density secondary batteries, and wrinkles and foil breaks frequently occur in the cold pressing process of the negative plate, which greatly affects the production efficiency of secondary batteries. Summary of the Invention
[0004] The object of the present application is to provide an electrodeposited copper foil and a manufacturing method thereof, a negative electrode plate, a secondary battery, a battery module, a battery pack, and a power consuming device, which are capable of improving the production efficiency of the electrodeposited copper foil and at the same time providing the electrodeposited copper foil with high isotropy and twin content, and superior electrical conductivity and mechanical performance.
[0005] According to a first aspect of the present application, a method for manufacturing an electrolytic copper foil is provided. The method includes step S10 of placing an anode and a cathode to be plated in a plating solution containing a twin growth agent in a plating bath, and step S20 of performing direct current plating on the plating solution under the condition that one or both of the ultrasonic waves with frequency f11 and the ultrasonic waves with frequency f12 and one or both of the ultrasonic waves with frequency f21 and the ultrasonic waves with frequency f22 are randomly switched alternately to obtain an electrolytic copper foil, where f11 > 40 kHz, 15 kHz < f12 ≤ 40 kHz, 0 kHz < f21 ≤ 15 kHz, and f22 = 0 kHz.
[0006] The method for manufacturing an electrolytic copper foil of the present application can grow a nano - copper structure having a high - degree selective orientation of (111) crystal planes in different directions at a high current density, improving production efficiency while enabling the electrolytic copper foil to have high isotropy, twin content, and better conductivity and mechanical properties.
[0007] In any embodiment of the present application, 40 kHz < f11 ≤ 100 kHz.
[0008] In any embodiment of the present application, in the process of plating to obtain the electrolytic copper foil, the occupation ratio of the total plating time under the conditions of the ultrasonic waves with frequency f11 and the ultrasonic waves with frequency f12 is 70% - 90%, and the occupation ratio of the total plating time under the conditions of the ultrasonic waves with frequency f21 and the ultrasonic waves with frequency f22 is 10% - 30%.
[0009] In any embodiment of the present application, in the process of plating to obtain the electrolytic copper foil, the occupation ratio of the total plating time under the conditions of the ultrasonic waves with frequency f11 and the ultrasonic waves with frequency f12 is 75% - 85%, and the occupation ratio of the total plating time under the conditions of the ultrasonic waves with frequency f21 and the ultrasonic waves with frequency f22 is 15% - 25%.
[0010] The total plating time under the conditions of the ultrasonic waves with frequency f11 and the ultrasonic waves with frequency f12 is within an appropriate range, the volume occupation ratio of the twinned crystal grains in the electrolytic copper foil is higher, and the volume occupation ratio of the (111) crystal plane is also higher.
[0011] In any embodiment of the present application, in the process of obtaining the electrolytic copper foil by plating, the plating time occupancy rate under the condition of f11 frequency ultrasonic is 40% to 90%. Optionally, the plating time occupancy rate under the condition of f11 frequency ultrasonic is 40% to 50%. The plating time occupancy rate under the condition of f11 frequency ultrasonic is within a suitable range, and the volume occupancy rate of twinned crystal grains in the electrolytic copper foil is higher, and the volume occupancy rate of the (111) crystal plane is also higher.
[0012] In any embodiment of the present application, in the process of obtaining the electrolytic copper foil by plating, the plating time occupancy rate under the condition of f12 frequency ultrasonic is 0-50%.Optionally, the plating time occupancy rate under the condition of f12 frequency ultrasonic is 40%-50%.
[0013] In any embodiment of the present application, in the process of obtaining the electrolytic copper foil by plating, the plating time occupancy rate under the condition of f21 frequency ultrasonic is 0% to 30%.Optionally, the plating time occupancy rate under the condition of f21 frequency ultrasonic is 5% to 25%.
[0014] In any embodiment of the present application, in the process of obtaining the electrolytic copper foil by plating, the plating time occupancy rate under the condition of f22 frequency ultrasonic is 0-10%.Optionally, the plating time occupancy rate under the condition of f22 frequency ultrasonic is 5%-10%.
[0015] In any embodiment of the present application, the current density of the direct current plating is 2 A / dm 2 ~80A / dm 2 Optionally, the current density of the direct current plating is 15 A / dm 2 ~80A / dm 2 The electrolytic copper foil of the present application can also realize plating at a high current density, thereby shortening the plating time and improving production efficiency.
[0016] In any embodiment of the present application, the twin growth agent comprises one or two of gelatin and polyethyleneimine.
[0017] In any embodiment of the present application, the plating solution is a sulfuric acid-copper sulfate plating solution, and the plating solution further comprises copper ions, sulfuric acid, and chloride ions.
[0018] In any embodiment of the present application, the concentration of copper ions in the plating solution is 50 g / L to 100 g / L. Optionally, the concentration of copper ions in the plating solution is 70 g / L to 80 g / L. The concentration of copper ions is within a suitable range, which can realize plating at a high current density and can also improve the plating effect and the quality of the plating layer.
[0019] In any embodiment of the present application, the concentration of sulfuric acid in the plating solution is 40 g / L to 70 g / L. Optionally, the concentration of sulfuric acid in the plating solution is 50 g / L to 60 g / L. When the concentration of sulfuric acid is within a suitable range, the plating effect and the quality of the plating layer are higher.
[0020] In any embodiment of the present application, the mass concentration of chloride ions in the plating solution is 20 ppm to 50 ppm. Optionally, the mass concentration of chloride ions in the plating solution is 30 ppm to 40 ppm. When the concentration of chloride ions is within a suitable range, the plating layer has higher leveling performance and gloss.
[0021] In any embodiment of the present application, the mass concentration of the twin growth agent in the plating solution is 50 ppm to 110 ppm. Optionally, the mass concentration of the twin growth agent in the plating solution is 70 ppm to 90 ppm. The concentration of the twin growth agent is within a suitable range, which can improve the quality of the plating layer and at the same time improve the isotropy and twin content of the electrolytic copper foil.
[0022] In an optional embodiment of the present application, the plating solution further comprises a leveling agent and a brightener.
[0023] In any embodiment of the present application, the leveling agent comprises a polypeptide protein.
[0024] In an optional embodiment of the present application, the brightener comprises one or more of sodium polydithiodipropane sulfonate and sodium 3-mercapto-1-propane sulfonate.
[0025] In any embodiment of the present application, the concentration of the leveling agent in the plating solution is 20ml / L to 40ml / L. Optionally, the concentration of the leveling agent in the plating solution is 25ml / L to 35ml / L. The concentration of the leveling agent is within a suitable range, which can improve the micro-dispersion ability of the plating solution and make the surface of the plating layer smoother.
[0026] In any embodiment of the present application, the concentration of the brightener in the plating solution is 10ml / L to 30ml / L. Optionally, the concentration of the brightener in the plating solution is 15ml / L to 25ml / L. The concentration of the brightener is within a suitable range, which can improve the gloss and gloss range of the plating layer.
[0027] According to a second aspect of the present application, there is provided an electrolytic copper foil, the electrolytic copper foil being produced by the method according to the first aspect of the present application.
[0028] In any embodiment of the present application, the volume occupancy rate of the electrolytic copper foil (111) crystal plane is ≧60%. Optionally, the volume occupancy rate of the electrolytic copper foil (111) crystal plane is ≧80%.
[0029] In any embodiment of the present application, the volume occupancy rate of twinned crystal grains in the electrolytic copper foil is ≧60%. Optionally, the volume occupancy rate of twinned crystal grains in the electrolytic copper foil is ≧80%.
[0030] In any embodiment of the present application, the room temperature tensile strength of the electrolytic copper foil is ≧50 kg / mm 2 Optionally, the room temperature tensile strength of the electrolytic copper foil is ≧60 kg / mm 2 It is.
[0031] In any embodiment of the present application, the electrolytic copper foil has a Vickers hardness of ≧180. Optionally, the electrolytic copper foil has a Vickers hardness of ≧190.
[0032] According to a third aspect of the present application, there is provided a negative electrode plate, the negative electrode plate comprising an electrolytic copper foil produced by the method of the first aspect of the present application, or an electrolytic copper foil according to the second aspect of the present application.
[0033] In any embodiment of the present application, the negative electrode plate further includes a negative electrode film layer disposed on at least one surface of the electrolytic copper foil, and the adhesive strength between the electrolytic copper foil and the negative electrode film layer is 10 N / m 2 ~20N / m 2 It is.
[0034] According to a fourth aspect of the present application, there is provided a secondary battery, the secondary battery including a negative electrode plate according to the third aspect of the present application.
[0035] According to a fifth aspect of the present application, there is provided a battery module, the battery module including a secondary battery according to the fourth aspect of the present application.
[0036] According to a sixth aspect of the present application, there is provided a battery pack, the battery pack including one of the secondary battery according to the fourth aspect of the present application and the battery module according to the fifth aspect.
[0037] According to a seventh aspect of the present application, there is provided a power consumption device, the power consumption device including at least one of a secondary battery according to the fourth aspect of the present application, a battery module according to the fifth aspect, and a battery pack according to the sixth aspect.
[0038] The battery module, battery pack and power consuming device of the present application include the secondary battery of the present application, and therefore have at least the same advantages as said secondary battery. [Brief description of the drawings]
[0039] In order to more clearly describe the technical solutions in the embodiments of the present application, the following briefly describes the drawings that need to be used in the embodiments of the present application. It is obvious that the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on the drawings without paying creative efforts. [Figure 1] FIG. 1 is a schematic diagram of one embodiment of a secondary battery of the present application. [Diagram 2] FIG. 1 is an exploded schematic view of an embodiment of a secondary battery of the present application. [Diagram 3] FIG. 1 is a schematic diagram of one embodiment of a battery module of the present application. [Figure 4] FIG. 1 is a schematic diagram of one embodiment of a battery pack of the present application. [Diagram 5] FIG. 5 is an exploded view of FIG. [Figure 6] 1 is a schematic diagram of an embodiment of a power consuming device in which the secondary battery of the present application is used as a power source. [Figure 7] FIG. 1 is a schematic diagram of an apparatus for producing an electrolytic copper foil according to the present application. [Figure 8] FIG. 2 is a schematic diagram of a test for the adhesive strength of a negative electrode plate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0040] Hereinafter, embodiments specifically disclosing the electrolytic copper foil and its manufacturing method, negative electrode plate, secondary battery, battery module, battery pack, and power consumption device of the present application will be described in detail with appropriate reference to the drawings. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of structures that are actually the same may be omitted. This is to avoid the following description becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.
[0041] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit that define the boundaries of the particular range. Such defined ranges may or may not include the end values, and may be arbitrarily combined, i.e., any lower limit and any upper limit may be combined to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also contemplated. It is to be noted that if minimum range values 1 and 2 and maximum range values 3, 4 and 5 are listed, the following ranges 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5 are all contemplated. In this application, unless otherwise stated, the numerical range "a-b" is a shorthand expression representing all real number combinations between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed herein, with "0-5" being merely a shorthand for combinations of these numbers. Also, when a parameter is described as an integer ≧2, this is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0042] Unless otherwise stated, all the embodiments and optional embodiments in the present application may be combined with each other to form a new technical solution.
[0043] Unless otherwise stated, all technical features and optional technical features in the present application may be combined with each other to form a new technical solution.
[0044] Unless otherwise stated, all steps in the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b) to mean that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method mentioned above further includes step (c) to mean that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.
[0045] Unless otherwise specified, the terms "comprise" and "comprises" referred to in this application may be open ended or closed ended. For example, the terms "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the listed ingredients.
[0046] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, any one of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), or both A and B are true (or exist).
[0047] Manufacturing method of electrolytic copper foil Electrodeposited copper foils manufactured by a direct current plating process have excellent mechanical properties, but the resulting electrolytic copper foils tend to be preferentially oriented in the (111) crystal plane, so that the electrolytic copper foils exhibit anisotropy either globally or locally, and there are always directions in which the mechanical properties are relatively weak. In order to eliminate the anisotropy of the electrolytic copper foils globally and locally, a method generally adopted in the prior art is to use a very small current density (e.g., 2 A / dm 2 ~8A / dm 2By performing electroplating, it is ensured that nano copper crystal grains can grow in various directions during the electroplating process. However, this method requires a very long electroplating time, has low production efficiency, and is not suitable for large-scale production.
[0048] As a result of the inventors' intensive research, a new method for manufacturing electrolytic copper foil is provided. It can grow a nano copper structure with a high preferential orientation of the (111) crystal plane in different directions at a high current density, improving production efficiency. At the same time, the obtained electrolytic copper foil has higher isotropy, twin content, and better electrical conductivity and mechanical properties.
[0049] Specifically, the method for manufacturing electrolytic copper foil in this application includes step S10 of placing an anode and a cathode to be electroplated in an electroplating solution containing a twin growth agent in an electroplating tank, and performing direct current electroplating on the electroplating solution under the condition that one or both of the ultrasonic waves with frequency f11 and f12 and one or both of the ultrasonic waves with frequency f21 and f22 are randomly and alternately converted to obtain an electrolytic copper foil, where f11 > 40 kHz, 15 kHz < f12 ≤ 40 kHz, 0 kHz < f21 ≤ 15 kHz, and f22 = 0 kHz in step S20.
[0050] The mechanical properties of the electrolytic copper foil obtained by the manufacturing method of this application in each direction are significantly better than those of ordinary copper foils, and the obtained electrolytic copper foil has higher isotropy and no weak direction in mechanical properties.
[0051] The twin grain boundary is a special low-energy interface, and its interface energy is approximately 1 / 10 of that of an ordinary large-angle grain boundary. Therefore, introducing twins into the material can obtain high strength and good electrical conductivity at the same time. A twin refers to two crystal grains or two parts of a single crystal grain that form a symmetric relationship of mirror images along a twin plane, and the relative orientation relationship, twin plane index, and twin direction of the two crystal parts that are twins to each other are all fixed.
[0052] Both normal grains (non-twinned grains) and twinned grains contain equiaxed grains and columnar grains. The equiaxed grains have a large grain boundary area, the distribution of impurities and defects is dispersed, and the orientation of the equiaxed grains is different, so the equiaxed grains are more uniform, stable, and non-directional. However, the equiaxed grains have developed dendrites and many microspheres, and the crystal structure after solidification is less dense. By refining the equiaxed grains, the distribution of impurities and defects can be better dispersed, and the performance of the crystal can be further improved. The finer the grains, the better the overall performance and the higher the fatigue strength. During the growth process of the columnar grains, the solidification area is narrow and its lateral growth is hindered, so the growth of the dendrites cannot be fully developed, there are few branches, the microspheres after crystallization and the impurities between the crystals are both small, and the crystal structure is dense. However, the columnar grains are coarse, have small grain boundary areas and are aligned, and therefore exhibit significant directionality, i.e., good vertical performance and poor horizontal performance.
[0053] During the plating process, the twin growth agent in the plating solution quickly adheres to other crystal planes (e.g., (101) crystal plane, (001) crystal plane) other than the (111) crystal plane of the nano-copper crystal grains, so that during the plating process, the nano-copper crystal grains grow along the close-packed stacking plane of the (111) crystal plane and inhibit the nano-copper crystal grains from growing along other crystal planes, so that the electrolytic copper foil has better electrical conductivity and mechanical performance.
[0054] During the plating process, with the application of ultrasound of different frequencies (one or two of f11 frequency ultrasound and f12 frequency ultrasound, and one or two of f21 frequency ultrasound and f22 frequency ultrasound), the nano-copper crystal grains grow along different directions, eliminating local anisotropy and growing a nano-copper structure with higher isotropy and twin content, and the mechanical properties in each direction of the resulting electrolytic copper foil are significantly superior to those of ordinary copper foil.
[0055] In the plating process, with ultrasonic waves of different frequencies, the size of the nano copper crystal grains obtained by plating is smaller and more uniform, the volume occupancy of the twinned crystal grains (including twinned equiaxed crystals and twinned columnar crystals) in the electrolytic copper foil is higher, and the volume occupancy of the (111) crystal plane is also higher. The electrolytic copper foil has higher isotropy, better conductivity and mechanical properties.
[0056] In the process of plating with ultrasonic waves of f11 frequency and f12 frequency, the tendency to generate twinned equiaxed crystals is stronger. In the process of plating with ultrasonic waves of f21 frequency and f22 frequency, the tendency to generate twinned columnar crystals is stronger. When ultrasonic waves of different frequencies are converted (i.e., frequency conversion), the growth of general crystal grains (i.e., non-twinned crystal grains) can be suppressed, and the growth of twinned crystal grains (including twinned equiaxed crystals and twinned columnar crystals) can be promoted. In addition, in the plating process, the conversion of ultrasonic waves of different frequencies (i.e., frequency conversion) can better promote the adhesion between the twin growth agent and other crystal planes (such as (101) crystal plane, (001) crystal plane) of the nano copper crystal grains other than the (111) crystal plane, and can provide a better environment for the nano copper crystal grains to grow along the (111) crystal plane. Therefore, the electrolytic copper foil not only has higher isotropy and twin content, but also further has better conductivity and mechanical properties.
[0057] If the frequency of the ultrasonic wave is too high, it may insufficiently adhere the twin growth agent to other crystal planes (such as (101) crystal plane, (001) crystal plane) of the nano copper crystal grains other than the (111) crystal plane, and may cause a decrease in the isotropy and the content of twinned crystal grains of the electrolytic copper foil. In some embodiments, optionally, 40 kHz < f11 ≤ 100 kHz. In particular, 40 kHz < f11 ≤ 60 kHz.
[0058] In this application, "frequency conversion" refers to conversion between any two of the following frequencies: f11 frequency ultrasound, f12 frequency ultrasound, f21 frequency ultrasound, and f22 frequency ultrasound. For example, conversion between f11 frequency ultrasound and f12 frequency ultrasound, conversion between f11 frequency ultrasound and f21 frequency ultrasound, conversion between f11 frequency ultrasound and f22 frequency ultrasound, conversion between f12 frequency ultrasound and f21 frequency ultrasound, conversion between f12 frequency ultrasound and f22 frequency ultrasound, and conversion between f21 frequency ultrasound and f22 frequency ultrasound. And, "frequency conversion" in this application does not include conversion from one f11 frequency ultrasound to another f11 frequency ultrasound, conversion from one f12 frequency ultrasound to another f12 frequency ultrasound, or conversion from one f21 frequency ultrasound to another f21 frequency ultrasound.
[0059] The "total number of frequency conversions" refers to the total number of conversions between any two of the following frequencies in the plating process: f11 frequency ultrasonic wave, f12 frequency ultrasonic wave, f21 frequency ultrasonic wave, and f22 frequency ultrasonic wave.
[0060] In some embodiments, in order to further remove the anisotropy of the electrolytic copper foil, the number of ultrasonic conversions (i.e., the number of frequency conversions) may be two or more in the process of obtaining the electrolytic copper foil by plating. As the number of frequency conversions increases, the content of non-twinned crystal grains in the electrolytic copper foil decreases. However, the number of frequency conversions is also not good if it is too high. Optionally, the number of ultrasonic conversions (i.e., the number of frequency conversions) per minute is 25 or less. In particular, the number of ultrasonic conversions (i.e., the number of frequency conversions) per minute is 2 or more and 10 or less.
[0061] In some embodiments, in the process of obtaining the electrolytic copper foil by plating, the occupancy rate of the total plating time under the conditions of f11 frequency ultrasonic and f12 frequency ultrasonic is 70% to 90%, and the occupancy rate of the total plating time under the conditions of f21 frequency ultrasonic and f22 frequency ultrasonic is 10% to 30%.
[0062] Under the conditions of f11 frequency ultrasonic and f12 frequency ultrasonic, the total plating time is within an appropriate range, and the volume fraction of the twinned crystal grains in the electrolytic copper foil is higher, and the volume fraction of the (111) crystal plane is also higher.
[0063] In some embodiments, optionally, the occupancy rate of the total plating time under conditions of f11 frequency ultrasound and f12 frequency ultrasound is 75% to 85%, and the occupancy rate of the total plating time under conditions of f21 frequency ultrasound and f22 frequency ultrasound is 15% to 25%.
[0064] In some embodiments, the plating time occupancy rate under the condition of f11 frequency ultrasonic is 40% to 90%. Optionally, the plating time occupancy rate under the condition of f11 frequency ultrasonic is 40% to 50%. When the plating time occupancy rate under the condition of f11 frequency ultrasonic is within a suitable range, the volume occupancy rate of twinned crystal grains in the electrolytic copper foil is higher, and the volume occupancy rate of the (111) crystal plane is also higher.
[0065] In some embodiments, the occupancy rate of the plating time under the condition of f12 frequency ultrasonic is 0 to 50%. Optionally, the occupancy rate of the plating time under the condition of f12 frequency ultrasonic is 40% to 50%.
[0066] In some embodiments, the occupancy rate of the plating time under the condition of f21 frequency ultrasonic waves is 0 to 30%. Optionally, the occupancy rate of the plating time under the condition of f21 frequency ultrasonic waves is 5% to 25%.
[0067] In some embodiments, the occupancy rate of the plating time under the condition of f22 frequency ultrasonic is 0 to 10%. Optionally, the occupancy rate of the plating time under the condition of f22 frequency ultrasonic is 5% to 10%.
[0068] In some embodiments, the DC plating is performed under conditions where the plating solution is accompanied by randomly alternating f11 frequency ultrasonic waves, f12 frequency ultrasonic waves, f21 frequency ultrasonic waves, and f22 frequency ultrasonic waves. In the process of obtaining the electrolytic copper foil by plating, the plating time occupancy rate under the condition of f11 frequency ultrasonic waves is 40% to 50%, the plating time occupancy rate under the condition of f12 frequency ultrasonic waves is 40% to 50%, the plating time occupancy rate under the condition of f21 frequency ultrasonic waves is 5% to 25%, and the plating time occupancy rate under the condition of f22 frequency ultrasonic waves is 5% to 10%.
[0069] In some embodiments, the current density of the direct current plating is 2 A / dm 2 ~80A / dm 2 It is.
[0070] The electrolytic copper foil of the present application, which has higher isotropy and twin content, and better electrical conductivity and mechanical performance, can also realize plating at a high current density, thereby shortening plating time and improving production efficiency. In some embodiments, the current density of direct current plating is 15 A / dm 2 ~80A / dm 2 For example, the current density of DC plating is 15A / dm 2 ~80A / dm 2 , 15A / dm 2 ~70A / dm 2 , 15A / dm 2 ~60A / dm 2 , 15A / dm 2 ~50A / dm 2 , 15A / dm 2 ~40A / dm 2 , 20A / dm 2 ~80A / dm 2 , 20A / dm 2 ~70A / dm 2 , 20A / dm 2 ~60A / dm 2 , 20A / dm 2 ~50A / dm 2 , 20A / dm 2 ~40A / dm 2 , 30A / dm 2 ~80A / dm2 , 30A / dm 2 ~70A / dm 2 , 30A / dm 2 ~60A / dm 2 , 30A / dm 2 ~50A / dm 2 , or 30A / dm 2 ~40A / dm 2 It is.
[0071] In some embodiments, the twin growth agent comprises one or two of gelatin and polyethyleneimine.
[0072] In some embodiments, the plating solution is a sulfuric acid-copper sulfate plating solution, the plating solution including a twin growth agent, copper ions, sulfuric acid, and chloride ions.
[0073] In some embodiments, the mass concentration of the twin growth agent in the plating solution is 50 ppm to 110 ppm. Optionally, the mass concentration of the twin growth agent in the plating solution is 70 ppm to 90 ppm. When the concentration of the twin growth agent is high, the plating effect and the quality of the plating layer are deteriorated, and when the concentration of the twin growth agent is low, the copper crystal grains cannot be inhibited from growing along the (101) crystal plane and the (001) crystal plane, and the content of twinned crystal grains in the electrolytic copper foil is low. When the concentration of the twin growth agent is within an appropriate range, the quality of the plating layer can be improved, and at the same time, the isotropy and twin content of the electrolytic copper foil can be improved.
[0074] In some embodiments, the concentration of sulfuric acid in the plating solution is 40 g / L to 70 g / L. Optionally, the concentration of sulfuric acid in the plating solution is 50 g / L to 60 g / L. When the concentration of sulfuric acid is high, the solubility of copper sulfate in the plating solution decreases, and the interface between the two phases is easily saturated. The excess copper ions and sulfate ions form copper sulfate and precipitate as crystals at the anode, inhibiting the normal dissolution process of the anode, and the anode is easily passivated. When the concentration of sulfuric acid is low, the plating layer is rough and the anode is also easily passivated. When the concentration of sulfuric acid is within a suitable range, the plating effect and the quality of the plating layer are higher.
[0075] In some embodiments, the concentration of copper ions in the plating solution is 50 g / L to 100 g / L. Optionally, the concentration of copper ions in the plating solution is 70 g / L to 80 g / L. When the concentration of copper ions is high, copper sulfate is likely to precipitate as crystals, and when the concentration of copper ions is low, the conductivity of the plating solution is low and the current density that can be used during plating is also low. When the concentration of copper ions is within an appropriate range, plating at a high current density can be achieved, and the effect of plating and the quality of the plating layer can be improved.
[0076] In the process of preparing the plating solution, the source of copper ions may be a copper salt, for example, copper sulfate.
[0077] In some embodiments, the mass concentration of chloride ions in the plating solution is 20 ppm to 50 ppm. Optionally, the mass concentration of chloride ions in the plating solution is 30 ppm to 40 ppm. When the concentration of chloride ions is high, the plating layer is likely to have hard spots, stripes, branching patterns, etc., which affect the leveling performance of the plating layer, and when the concentration of chloride ions is low, the gloss of the plating layer is reduced. When the concentration of chloride ions is within an appropriate range, the plating layer has higher leveling performance and gloss.
[0078] In the process of preparing the plating solution, the source of chloride ions may be hydrochloric acid, sodium chloride, or potassium chloride.
[0079] In some embodiments, the plating solution further comprises an aqueous solvent.
[0080] In some embodiments, the plating solution further comprises a leveling agent and a brightener. The leveling agent can improve the micro-dispersion ability of the plating solution and make the surface of the plating layer smoother, and the brightener can improve the gloss and gloss range of the plating layer.
[0081] Optionally, the leveling agent comprises a polypeptide protein.
[0082] Optionally, the brightener comprises one or more of sodium polydithiodipropane sulfonate and sodium 3-mercapto-1-propane sulfonate.
[0083] In some embodiments, the concentration of the leveling agent in the plating solution is 20 ml / L to 40 ml / L. Optionally, the concentration of the leveling agent in the plating solution is 25 ml / L to 35 ml / L. When the content of the leveling agent is low, the surface of the electrolytic copper foil obtained by plating is not smooth enough and is prone to fine pits, and when the content of the leveling agent is high, the brittleness of the electrolytic copper foil increases and the toughness is prone to decrease.
[0084] In some embodiments, the concentration of the brightener in the plating solution is 10 ml / L to 30 ml / L. Optionally, the concentration of the brightener in the plating solution is 15 ml / L to 25 ml / L. When the content of the brightener is low, the electrolytic copper foil obtained by plating has low gloss and narrow gloss range, and when the content of the brightener is high, the brittleness of the electrolytic copper foil increases and the toughness is likely to decrease.
[0085] In some embodiments, the temperature of the DC plating is room temperature, for example 25°C ± 5°C.
[0086] In some embodiments, the anode is high purity cast copper, optionally with the exterior surface of the high purity cast copper further encased in a titanium basket.
[0087] In some embodiments, the cathode is a high-purity titanium plate, and the main component of the titanium plate is titanium. Of course, other materials of the cathode may be used as the base for plating deposition, such as metallic copper, metallic nickel, etc.
[0088] In some embodiments, before performing step S10, the method for producing the electrolytic copper foil further includes the step of degreasing, acid washing, and water washing the cathode to remove surface oil stains, oxide layers, and the like.
[0089] In some embodiments, before performing step S10, the method for producing the electrolytic copper foil further includes a step of externally attaching an ultrasonic generator below the plating bath. The ultrasonic generator of the present application can be directly placed below the original plating bath, and there is no need to replace the bath body of the plating bath, so the process is simplified and production efficiency is improved. The number of ultrasonic generators can be one or more, for example, two or three.
[0090] In some embodiments, the method for producing the electrolytic copper foil further comprises a step of separating the plated electrolytic copper foil from the cathode.
[0091] The electrolytic copper foil obtained by the manufacturing method of the present application has higher isotropy.
[0092] In some embodiments, the volume occupancy of the electrolytic copper foil (111) crystal plane is ≧60%. Optionally, the volume occupancy of the electrolytic copper foil (111) crystal plane is ≧70%. Further optionally, the volume occupancy of the electrolytic copper foil (111) crystal plane is ≧80%.
[0093] In some embodiments, the volume occupancy of the twinned crystal grains in the electrolytic copper foil is ≧60%. Optionally, the volume occupancy of the twinned crystal grains in the electrolytic copper foil is ≧70%. Further optionally, the volume occupancy of the twinned crystal grains in the electrolytic copper foil is ≧80%.
[0094] The electrolytic copper foil obtained by the manufacturing method of the present application has excellent electrical conductivity and mechanical properties.
[0095] In some embodiments, the room temperature tensile strength of the electrolytic copper foil is ≧50 kg / mm 2 Optionally, the room temperature tensile strength of the electrolytic copper foil is ≧55 kg / mm 2Further optionally, the room temperature tensile strength of the electrolytic copper foil is ≧60 kg / mm 2 It is.
[0096] In some embodiments, the electrolytic copper foil has a Vickers hardness of ≧180. Optionally, the electrolytic copper foil has a Vickers hardness of ≧185. Further optionally, the electrolytic copper foil has a Vickers hardness of ≧190.
[0097] In some embodiments, the electrolytic copper foil has a thickness of 4 μm to 20 μm.
[0098] secondary battery A secondary battery is also called a rechargeable battery or storage battery, and refers to a battery that can be continuously used by activating the active material through a charging method after the battery is discharged.
[0099] A secondary battery generally includes a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. During the charge and discharge process of the battery, active ions (e.g., lithium ions, sodium ions) shuttle between the positive electrode plate and the negative electrode plate to absorb and release. The separator is installed between the positive electrode plate and the negative electrode plate, and mainly serves to prevent short circuits between the positive and negative electrodes and allows the active ions to pass through. The electrolyte mainly serves to conduct the active ions between the positive and negative electrode plates.
[0100] [Negative plate] The secondary battery includes a negative electrode plate, which generally includes a negative electrode current collector and a negative electrode film layer that is disposed on at least one surface of the negative electrode current collector and includes a negative electrode active material. For example, the negative electrode current collector has two surfaces that face each other in the thickness direction of the negative electrode current collector, and the negative electrode film layer is laminated on either one or both of the two facing surfaces of the negative electrode current collector.
[0101] In the negative electrode plate of the present application, the negative electrode film layer generally includes a negative electrode active material, an optional adhesive, an optional conductive agent, and other optional auxiliary agents. The negative electrode film layer is generally formed by applying a negative electrode slurry onto a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is generally formed by dispersing the negative electrode active material, the optional conductive agent, the optional adhesive, the optional auxiliary agent, etc. in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water. The type and content of the conductive agent and the adhesive are not specifically limited and may be selected according to actual needs. Exemplarily, the conductive agent may include one or more of superconducting carbon, carbon black (e.g., acetylene black, ketjen black, etc.), carbon spots, carbon nanotubes, graphene, and carbon nanofibers. Exemplarily, the adhesive may include one or more of styrene butadiene rubber (SBR), water-soluble unsaturated resin (SR-1B), water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). Other optional auxiliary agents may include thickeners (e.g., sodium carboxymethyl cellulose CMC-Na), PTC thermistor materials, and the like.
[0102] In some embodiments, the type of the negative electrode active material is not specifically limited, and may be a negative electrode active material for secondary batteries well known in the art. Exemplarily, the negative electrode active material may include one or more of graphite, soft carbon, hard carbon, mesocarbon microbeads, carbon fiber, carbon nanotube, silicon-based material, tin-based material, and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon carbon composite, silicon nitrogen composite, and silicon alloy material. The tin-based material may include one or more of elemental tin, stannic acid compound, and tin alloy material. The present application is not limited to these materials, and may further use other conventionally known materials that can be used as a negative electrode active material for secondary batteries. These negative electrode active materials may be used alone or in combination of two or more.
[0103] In the negative electrode plate of the present application, the negative electrode current collector may be an electrolytic copper foil obtained by the manufacturing method of the present application.
[0104] In some embodiments, the adhesion between the negative electrode current collector and the negative electrode film layer is 10 N / m 2 ~20N / m 2 It is.
[0105] When the negative electrode current collector adopts the electrolytic copper foil manufactured according to the first embodiment of the present application or the electrolytic copper foil according to the second embodiment of the present application, the adhesive strength of the negative electrode plate is significantly higher than that of the negative electrode current collector adopting an ordinary copper foil as the negative electrode plate. A possible reason is that the electrolytic copper foil obtained by the manufacturing method of the present application has finer crystal grains, so there are more chemical bonds on the surface of the electrolytic copper foil, and the adhesive strength with the negative electrode active material, etc. is stronger.
[0106] [Positive plate] The present application provides a positive electrode plate, which includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector and containing a positive electrode active material. For example, the positive electrode current collector has two surfaces facing each other in a thickness direction thereof, and the positive electrode film layer is disposed on either one or both of the two facing surfaces of the positive electrode current collector.
[0107] In the positive electrode plate of the present application, the positive electrode film layer generally includes a positive electrode active material, an optional adhesive, and an optional conductive agent. The positive electrode film layer is generally formed by applying a positive electrode slurry onto a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is generally formed by dispersing the positive electrode active material, the optional conductive agent, the optional adhesive, and any other components in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP). Exemplarily, the adhesive used in the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic ester resin. Exemplarily, the conductive agent used in the positive electrode film layer may include one or more of superconducting carbon, acetylene black, carbon black, ketjen black, carbon spots, carbon nanotubes, and graphene carbon nanofibers.
[0108] In the positive electrode plate of the present application, the positive electrode current collector may adopt a metal foil sheet or a composite current collector. As an example of the metal foil sheet, the positive electrode current collector may adopt an aluminum foil. The composite current collector may include a polymeric material substrate and a metal material layer formed on at least one surface of the polymeric material substrate. Exemplarily, the metal material may be selected from one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. Exemplarily, the polymeric material substrate may be selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0109] In the positive electrode plate of the present application, the positive electrode film layer includes a positive electrode active material, and the positive electrode active material may be any positive electrode active material for secondary batteries that is well known in the art.
[0110] It should be explained that the secondary battery in the present application may be a lithium ion battery, a sodium ion battery.
[0111] When the secondary battery of the present application is a lithium ion battery, optionally, the positive electrode active material may include one or more of lithium transition metal oxides, lithium-containing phosphates with an olivine structure, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and their respective modified compounds. The present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for lithium ion batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more.
[0112] For example, the positive electrode active materials for lithium-ion batteries are LiCoO2, LiNiO2, LiMnO2, LiMn2O4, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 It may be selected from one or more of O2, LiFePO4 (LFP) and LiMnPO4.
[0113] When the secondary battery of the present application is a sodium ion battery, optionally, the positive electrode active material is a transition metal oxide Na x MO2 (M is a transition metal, optionally selected from one or more of Mn, Fe, Ni, Co, V, Cu, Cr, and 0 < x ≦ 1), a polyanion material (such as phosphate, fluorophosphate, pyrophosphate, sulfate, etc.), a Prussian blue material, etc. may be selected, but the present application is not limited to these materials, and other materials that can be used as the positive electrode active material of a sodium ion battery may also be used. These positive electrode active materials may be used alone, or two or more of them may be used in combination.
[0114] Optionally, the positive electrode active material of the sodium ion battery is NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, NaNi 1 / 2 Ti 1 / 2 O2, NaNi 1 / 2 Mn 1 / 2 O2, Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2, NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, a Prussian blue material, and materials of the general formula A a M b (PO4) c O x Y 3-x may be selected from one or more of them. A is selected from one or more of H + , Li + , Na + , K + and NH4 + , M is a transition metal cation, optionally selected from one or more of V, Ti, Mn, Fe, Co, Ni, Cu and Zn, Y is a halogen anion, optionally selected from one or more of F, Cl and Br, 0 < a ≦ 4, 0 < b ≦ 2, 1 ≦ c ≦ 3, 0 ≦ x ≦ 2.
[0115] In some embodiments, the modified compound of each of the positive electrode active materials may be a positive electrode active material that has been doped, surface-coated, or doped and surface-coated at the same time.
[0116] [Electrolyte] The electrolyte serves to conduct active ions between the positive and negative plates. The secondary battery of the present application has no specific limitations on the type of electrolyte, and may be selected according to need. For example, the electrolyte may be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolytic solution).
[0117] In some embodiments, the electrolyte employs an electrolyte solution, the electrolyte solution including an electrolyte salt and a solvent.
[0118] In some embodiments, the type of electrolyte salt is not specifically limited, and can be selected according to actual needs. When the secondary battery of the present application is a lithium ion battery, optionally, the electrolyte salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonimide (LiFSI), lithium bistrifluoromethanesulfonimide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluoro(oxalato)borate (LiDFOB), lithium bis(oxalato)borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluoro(oxalato)borate (LiDFOP) and lithium tetrafluoro(oxalato)phosphate (LiTFOP). When the secondary battery of the present application is a sodium ion battery, optionally, the electrolyte salt may be selected from one or more of NaPF6, NaClO4, NaBCl4, NaSO3CF3, and Na(CH3)C6H4SO3.
[0119] In some embodiments, there is no specific limitation on the type of solvent, which can be selected according to actual needs. Exemplarily, the solvent may be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfone (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).
[0120] In some embodiments, optionally, the solvent is a non-aqueous solvent.
[0121] In some embodiments, the electrolyte solution optionally further includes additives. For example, the additives may include an anode film-forming additive, a cathode film-forming additive, or an additive that can improve some performance of the battery, such as an additive that improves the overcharge performance of the battery, an additive that improves the high temperature performance of the battery, or an additive that improves the low temperature performance of the battery.
[0122] [Separator] A separator is further included in secondary batteries using an electrolyte solution and some secondary batteries using a solid electrolyte. The separator is disposed between the positive and negative plates and plays a role of isolating them. The present application does not particularly limit the type of separator, and any well-known separator with a porous structure having good chemical stability and mechanical stability may be selected. In some embodiments, the material of the separator may be selected from one or more of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layered thin film or a multi-layered composite thin film. When the separator is a multi-layered composite thin film, the materials of each layer may be the same or different.
[0123] In some embodiments, the positive and negative plates and the separator may be fabricated into an electrode assembly by a winding or lamination process.
[0124] In some embodiments, the secondary battery may include an exterior case that may be used to package the electrode assembly and electrolyte.
[0125] In some embodiments, the exterior of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The exterior of the secondary battery may be a soft package, such as a bag-type soft package. The material of the soft package may be one or more of plastics, such as polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0126] The present application does not particularly limit the shape of the secondary battery, which may be cylindrical, rectangular or any other shape. Figure 1 shows a secondary battery 5 with a rectangular structure as an example.
[0127] In some embodiments, referring to FIG. 2, the exterior may include a housing 51 and a cover plate 53. The housing 51 may include a bottom plate and a side plate connected on the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 is for covering the opening and sealing the receiving cavity. The positive electrode plate, the negative electrode plate and the separator may form an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. An electrolyte is infiltrated into the electrode assembly 52. The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and may be adjusted according to demand.
[0128] In some embodiments, the secondary batteries can be assembled into a battery module, and the number of secondary batteries included in the battery module can be multiple, with the specific number being adjustable based on the application and capacity of the battery module.
[0129] Fig. 3 shows an example of a battery module 4. Referring to Fig. 3, in the battery module 4, the secondary batteries 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the secondary batteries 5 may be fixed by fasteners.
[0130] Optionally, the battery module 4 may further include a housing having an accommodating space, and the multiple secondary batteries 5 are accommodated in the accommodating space.
[0131] In some embodiments, the battery modules can be further assembled into a battery pack, and the number of battery modules included in the battery pack can be adjusted based on the application and capacity of the battery pack.
[0132] 4 and 5 show an example of a battery pack 1. Referring to Fig. 4 and Fig. 5, the battery pack 1 may include a battery case and a plurality of battery modules 4 installed in the battery case. The battery case includes an upper case 2 and a lower case 3, and the upper case 2 covers the lower case 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery case in any manner.
[0133] power consumption equipment An embodiment of the present application further provides a power consuming device, the power consuming device including at least one of the secondary battery, the battery module, and the battery pack of the present application. The secondary battery, the battery module, or the battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may be, but is not limited to, a mobile device (e.g., a mobile phone, a laptop, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0134] The power consumption device can select a secondary battery, a battery module or a battery pack according to the usage demand.
[0135] 6 shows an example of a power consuming device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be adopted to meet the high power and high energy density requirements of the power consuming device.
[0136] Another example of the power consuming device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a power consuming device is generally required to be lightweight and may employ a secondary battery as a power source.
[0137] Working Example The following examples are provided to more specifically describe the contents disclosed in this application, and these examples are used merely for illustrative purposes, and it is obvious to those skilled in the art that various modifications and changes can be made within the scope of the contents disclosed in this application. Unless otherwise indicated, all parts, percentages, and ratios reported in the following examples are all by weight, all reagents used in the examples are all commercially available or can be synthesized by common methods, and can be used directly without further treatment, and all equipment used in the examples can be commercially available.
[0138] Example 1 (1) Preparation of plating solution Copper sulfate, sulfuric acid, sodium chloride, twin growth agent, leveling agent, and brightener are dissolved in water and thoroughly stirred to mix uniformly, where the concentrations of each component are 75 g / L for copper ions, 55 g / L for sulfuric acid, 35 ppm for chlorine ions, 85 ppm for twin growth agent, 30 ml / L for leveling agent, and 20 ml / L for brightener, respectively.
[0139] (2) Direct current plating Referring to FIG. 7, the anode plate and the cathode roller to be plated were immersed in the plating solution at 25±5° C., and two ultrasonic generators were placed at the bottom of the plating tank. DC plating was performed under ultrasonic conditions, and the current density was 30 A / dm 2 The total plating time is 45 min. In the plating process, the ultrasonic frequency conversion method is as follows: 28kHz-45kHz-28kHz-0kHz-10kHz-45kHz are converted in sequence for multiple cycles, the total number of frequency conversions is 269, and the ultrasonic time occupancy rates of different frequency ultrasonic waves are 15%-20%-25%-5%-15%-20% respectively. The thickness of the electrolytic copper foil obtained after plating is 6 μm.
[0140] Examples 2 to 12 The manufacturing method of the electrolytic copper foil is similar to that of Example 1, with the difference being that the relevant parameters in the plating process are controlled, as shown in Table 1.
[0141] Comparative Examples 1 to 4 The manufacturing method of the electrolytic copper foil is similar to that of Example 1, except that single-frequency ultrasonic waves are used in the plating process. The specific parameters are as shown in Table 1.
[0142] Testing part (1) Different crystal planes of electrolytic copper foil and different crystal grain volume occupancies Obtained by Electron Backscattered Diffraction.
[0143] (2) Roughness of electrolytic copper foil Test of electrodeposited copper foil surface roughness Rz: Measured using a contact type roughness meter in accordance with the JIS94 standard.
[0144] (3) Electrical conductivity of electrolytic copper foil Conductivity of electrolytic copper foil (%IACS, International Annealed Copper Standard) test: The sheet resistance was measured using a four-point probe and calculated by substituting the thickness of the electrolytic copper foil (the copper foil thickness was converted according to the single weight).
[0145] (4) Tensile strength of electrolytic copper foil Tensile strength RTS test of electrolytic copper foil: After plating was completed, the foil was left for at least 24 hours, and then a test piece was punched out into a dumbbell shape (gauge length 50 mm, width 3 mm) and then tested.
[0146] (5) Vickers hardness of electrolytic copper foil Testing the Vickers hardness Hv of electrolytic copper foil: An electronic universal testing machine was used to press a diamond pyramid indenter with a vertex angle of 136° into the surface of the electrolytic copper foil with a load of up to 120 kg, and the load value was divided by the surface area of the indentation pit to obtain the Vickers hardness Hv of the electrolytic copper foil.
[0147] (6) Adhesive strength of negative plate The negative electrode active material graphite, the conductive agent conductive carbon, the adhesive styrene butadiene rubber, and the thickener carboxymethylcellulose sodium (CMC-Na) were mixed in a mass ratio of 96.8:0.4:1.8:1, and then the solvent deionized water was added and thoroughly stirred by a method well known in the art to form a negative electrode slurry. The negative electrode slurry was uniformly applied onto the electrolytic copper foils of Examples 1 to 12 and Comparative Examples 1 to 4, and after drying, a negative electrode film layer was obtained, and a negative electrode plate was obtained through a cold pressing process. The compaction density of the negative electrode plate was 1.68 g / cm. 3 The coating density is 134 g / m 2 It is.
[0148] FIG. 8 is a schematic diagram of the test of the adhesive strength of the negative electrode plate. As shown in FIG. 8(a), first, a steel plate 410 is prepared, and the size of the steel plate is 30 mm wide x 100 mm long. As shown in FIG. 8(b), a double-sided tape 420 is prepared, and the size of the double-sided tape 420 is 20 mm wide x 30 mm long. The double-sided tape 420 is attached onto the steel plate 410, and one short side of the double-sided tape 420 and one short side of the steel plate 410 are aligned. As shown in FIG. 8(c), a plate 430 to be tested is prepared, and the size of the plate 430 to be tested is 30 mm wide x 30 mm long. The plate 430 to be tested is placed on the double-sided tape 420, and the coated surface of the plate 430 faces the double-sided tape 420, and one short side of the plate 430 to be tested and one short side of the steel plate 410 are aligned. Since the length of the electrode plate 430 to be tested is longer than the length of the double-sided tape 420, some areas of the electrode plate 430 to be tested are not adhered to the double-sided tape. As shown in FIG. 8(d), the steel plate 410 is fixed to the base of a tensile tester, the end of the electrode plate 430 to be tested that is not adhered to the double-sided tape is clamped by a jig, and the jig is pulled toward the other end (in the direction indicated by the arrow), so that the direction of the tensile force is parallel to the strength direction of the steel plate 410 and is in close contact with the surface of the steel plate 410. During the pulling process, the electrode plate 430 is gradually peeled off from the steel plate by pulling. During the pulling process, the pulling speed of the jig is 50 mm / min. During the pulling process, the tensile force of the jig is recorded, and after the tensile force becomes stable, it is peeled off by 70 mm, and the average tensile force at the peeled length is taken as the adhesive force.
[0149] Table 1 shows the parameters of Examples 1-12 and Comparative Examples 1-4, and Tables 2 and 3 show the test results of Examples 1-12 and Comparative Examples 1-4.
[0150] [Table 1]
[0151] [Table 2]
[0152] [Table 3]
[0153] As can be seen from the data results in Table 2, in plating at different high speed current densities, the electrodeposited copper foils of Examples 1 to 12 all grew along the (111) crystal plane of the closest packed plane at a high rate, the isotropy of the electrodeposited copper foils was higher, and the content of twinned crystal grains (including twinned equiaxed crystals and twinned columnar crystals) in the electrodeposited copper foils was also higher, and the electrodeposited copper foils were more stable, denser, and had better mechanical properties.
[0154] As can be seen from the data results in Table 3, the electrodeposited copper foil produced by the method of the present application has significantly improved tensile strength and Vickers hardness, and can significantly reduce the probability of foil breakage and wrinkles in the negative electrode plate during the secondary battery manufacturing process.
[0155] In addition, as can be seen from the data results in Table 3, when the electrolytic copper foil manufactured by the method of the present application is applied to a negative electrode plate, the adhesive strength of the negative electrode plate can be further improved and the probability of powder falling off of the negative electrode film layer can be reduced.
[0156] It should be noted that the present application is not limited to the above embodiment. The above embodiment is merely an example, and any embodiment having substantially the same configuration as the technical idea and having similar actions and effects within the scope of the technical proposal of the present application is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can conceive of to the embodiment are implemented within the scope of the gist of the present application, and other forms constructed by combining some of the components in the embodiment are also included in the scope of the present application.
Claims
1. A method for producing an electrolytic copper foil, comprising the steps of: Step S10: placing the anode and the cathode to be plated in a plating bath in a plating solution containing a twin growth agent, the twin growth agent including one or both of gelatin and polyethyleneimine; and a step S20 of performing DC plating under conditions in which one or two of f11 frequency ultrasonic waves and f12 frequency ultrasonic waves, and one or two of f21 frequency ultrasonic waves and f22 frequency ultrasonic waves, which are randomly alternated, are added to the plating solution to obtain an electrolytic copper foil, in which 40 kHz < f11 ≦ 100 kHz, 15 kHz < f12 ≦ 40 kHz, 0 kHz < f21 ≦ 15 kHz, and f22 = 0 kHz are satisfied; In the process of obtaining the electrolytic copper foil by plating, the occupancy rate of the total plating time under the condition of f11 frequency ultrasonic wave and f12 frequency ultrasonic wave is 70% to 90%, and the occupancy rate of the total plating time under the condition of f21 frequency ultrasonic wave and f22 frequency ultrasonic wave is 10% to 30%; In the process of obtaining the electrolytic copper foil by plating, the number of ultrasonic conversions is 2 or more, and the number of ultrasonic conversions per minute is 25 or less.
2. The method described in claim 1, wherein, in the process of plating to obtain the electrolytic copper foil, the occupancy rate of the total plating time under conditions of f11 frequency ultrasound and f12 frequency ultrasound is 75% to 85%, and the occupancy rate of the total plating time under conditions of f21 frequency ultrasound and f22 frequency ultrasound is 15% to 25%.
3. In the process of obtaining the electrolytic copper foil by plating, The plating time occupancy rate under the condition of f11 frequency ultrasonic is 40 to 90%, and / or The plating time occupancy rate under the condition of f12 frequency ultrasonic is 0 to 50%, and / or The plating time occupancy rate under the condition of f21 frequency ultrasonic is 0 to 30%, and / or The method according to claim 1, wherein the occupancy rate of plating time under the condition of f22 frequency ultrasonic is 0 to 10%.
4. The current density of the direct current plating is 2 A / dm 2 ~80A / dm 2 The method of claim 1, wherein
5. The plating solution is a sulfuric acid-copper sulfate plating solution, and the plating solution further contains copper ions, sulfuric acid, and chloride ions; The concentration of copper ions in the plating solution is 50 g / L to 100 g / L; The concentration of sulfuric acid in the plating solution is 40 g / L to 70 g / L; The mass concentration of chloride ions in the plating solution is 20 ppm to 50 ppm; 2. The method according to claim 1, wherein the mass concentration of the twin growth agent in the plating solution is 50 ppm to 110 ppm.
6. The plating solution further includes a leveling agent and a brightener, the leveling agent comprises a polypeptide protein, and the brightening agent comprises one or more of sodium polydithiodipropane sulfonate and sodium 3-mercapto-1-propane sulfonate; The concentration of the leveling agent in the plating solution is 20 ml / L to 40 ml / L; 2. The method of claim 1, wherein the concentration of the brightener in the plating solution is 10 ml / L to 30 ml / L.
7. 7. Use of the method according to any one of claims 1 to 6 in the manufacture of negative plates.
8. Use of the method according to any one of claims 1 to 6 in the manufacture of a secondary battery.
9. Use of a method according to any one of claims 1 to 6 in the manufacture of a battery module.
10. Use of the method according to any one of claims 1 to 6 in the manufacture of a battery pack.
11. Use of a method according to any one of claims 1 to 6 in the manufacture of an electrical power consuming device.
Citation Information
Patent Citations
Production method of copper foil with low warping value
CN106544704A
Low-temperature rapid manufacturing method of unidirectional high-temperature-resistant welded joint
CN112317972A
Electrolytic copper foil, and method of manufacturing the same
JP2002053993A
Copper foil, electrode for secondary battery, secondary battery, and printed circuit board
JP2013133514A
Electrolytic copper foil, lithium ion secondary battery negative pole electrode, and lithium ion secondary battery
JP2014009365A